The interpoint - Fineza, Rodolfo II B.; Santos, Frederick C. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The Interpoint is a proposed Transport Interchange in the center of the Quezon City Modal Transfer Hub- Cubao. It aims to improve the current transportation system in providing an effective interchange which integrates different movement patterns in Cubao area: vehicular and pedestrian flow. The Interpoint is a passenger-oriented space which highlights inter-connectivity of different transportation modes in Cubao. The project is designed to uplift the commuter experience given the existing transport systems in the metro through livable, green and welcoming spaces connected with means of movement.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Urban transportation; Urban transportation -- Quezon City -- Philippines